Cloning and targeted mutations of G alpha 7 and G alpha 8, two developmentally regulated G protein alpha-subunit genes in Dictyostelium. - Wu, L (1994)
GTP-binding protein (G protein)-mediated signal transduction pathways play essential roles during the aggregation and differentiation process of Dictyostelium. In addition to the five known G protein alpha-subunit genes, we recently identified three novel alpha-subunit genes, G alpha 6, G alpha 7, and G alpha 8, using the polymerase chain reaction technique. We present here a more complete analysis of G alpha 7 and G alpha 8. The cDNAs of these two genes were cloned, and their complete nucleotide sequences were determined. Sequence analyses indicate that G alpha 8 possesses some unusual features. It lacks the "TCATDT" motif, a sequence of amino acids highly conserved among G alpha subunits, and has an additional 50 amino acids at its C-terminus consisting of long stretches of asparagine. Moreover, G alpha 8 is unusually resistant to protease digestion, which may indicate a slow GTP hydrolysis rate. The possible functions of these alpha-subunits were assessed by generating mutants lacking G alpha 7 or G alpha 8 by gene targeting through homologous recombination and by overexpressing G alpha 7 or G alpha 8 protein. Overexpression of G alpha 7 resulted in abnormal morphogenesis starting at the slug stage, whereas analysis of the other strains failed to reveal any obvious growth or developmental defects under either normal or stressful conditions. The implications of these results are discussed.